2015
DOI: 10.4314/ajtcam.v12i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial activities of different plants extracts against <i>Staphylococcus aureus</i> isolated from soccer player’s shoes and knowledge and applications about foot hygiene of the soccer players

Abstract: Background: Microorganisms most commonly attack the feet. Bacteria have an easier entry into the athlete's epidermis. Staphylococcus aureus, commonly found on the skin or in the nose. The purpose of the study was to research the lack of knowledge on the antibacterial and antioxidant effects of different plants extracts and to report existing knowledge on hygiene of sports equipment and that of soccer players. Materials and Methods: The bacteria were isolated from soccer player's shoes (n=28) from Balıkesir Spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…DPPH radical scavenging activity of the flowers (0.114 mg/ml) was higher than that of the fruits (0.291 mg/ml). Similarly, Okmen (2015) reported higher radical scavenging activity (using ABTS method) in A. andrachne flowers than in the leaves. Furthermore, Kırca & Arslan (2008) and Ergün et al (2014) also reported high DPPH radical scavenging activity in A. andrachne flowers and leaves.…”
Section: Resultsmentioning
confidence: 84%
“…DPPH radical scavenging activity of the flowers (0.114 mg/ml) was higher than that of the fruits (0.291 mg/ml). Similarly, Okmen (2015) reported higher radical scavenging activity (using ABTS method) in A. andrachne flowers than in the leaves. Furthermore, Kırca & Arslan (2008) and Ergün et al (2014) also reported high DPPH radical scavenging activity in A. andrachne flowers and leaves.…”
Section: Resultsmentioning
confidence: 84%
“…rhoeadifolia using DPPH (IC 50 = 0.26 mg/mL) and TBARS assays (MDA level = 4.54 nmol/mL) [ 34 ]. The methanolic extract of C. sancta [ 35 ] was evaluated for its antioxidant capacity with the ABTS decolorization assay and alsoshowed promising results, while the infusion fromaerial parts of C. foetida L. [ 35 ] showed moderate activity (DPPH method). Lastly, the hydro–alcoholic extract of C. vesicaria subsp.…”
Section: Resultsmentioning
confidence: 99%
“…O extrato etanólico também foi inativo contra E. coli e B. cereus na CIM = 12.500 µg/mL. Nos estudos de Okmen 45 , o extrato metanólico das folhas de P. major apresentou-se inativo (CIM = 1.625 µg/mL) contra diferentes cepas de S. aureus.…”
Section: Discussionunclassified